The relation of physical balance and energy value in sheep rations. A comparison of different roughages combined with two levels of concentrate allowance for wintering ewe lambs. - Bell, T.D.; Cox, R.F.; Richardson, D.; Parrish, D.B.; Hughes, J.S. (Kansas Agricultural Experiment Station, 2012)
In the winter of 1951-52 a test was made of the response of ewe lambs to rations containing different proportions of roughages, and concentrates as well as of their response to rations made up of some of the more common roughages found in Kansas. The ewe lambs, which were of three breeding types, were secured from Southern Utah; they will be used in the subsequent breeding studies. The lambs were divided into six lots with uniform distribution of the lambs of different breeding into the various lots. The roughages compared were long alfalfa hay, ground Atlas stover, and Atlas silage in combination with prairie hay. Cottonseed meal was added to supply protein to all of the rations, and milo grain was also given in those three lots where a higher ratio of crude fiber to T.D.N. was desired. Originally, the experiments were planned for two lots of lambs to receive each of the three roughages or a combination of roughages, One of the two lots was fed a ration with a fiber-T.D.N. ratio of 1: 2, and the other lot a crude fiber-T.D.N. ratio of 1: 3. Because of limited digestive capacities and the lack of palatability of some of the roughages used, these ratios could not be maintained. The accompanying table gives the rations fed in the various lots, the crude fiber-T.D.N. rations and the response of the lambs, to the various rations.
Keywords: Sheep; Energy value; Roughages; Fiber-T.D.N.